Implementasi Konsep Madrasatul Ula Pada Pendidikan Agama Dalam Keluarga Perantau - Muflihatul Marfu’ah; Muru’atul Afifah (At-Tarbiyat, 2020)
Family education is the first and foremost education for children. More specifically a mother, like a mother who is often referred to as Al-Umm Madrasatul ula (first school) for children. However, in Pekamban Daya Village, Praga Subdistrict, Sumenep, Madura there are some mothers who work and migrate so that they cannot meet their children everyday. Then how can a mother carry out her role as a madrasatul ula. As for the results of this study, the role of mothers as madrasatul ula is to provide attention, love, prayer and monitor children's development by telephon. However, in their daily lives, the role of the mother is taken over by the family who is accompanying the child at home, namely kayeh, nyaih and bibi’. As for the implementation of religious education that is implemented by migrant families, in addition to children being taught by their companion family at home, children are also enrolled in TPQ or Mushalah, and formal education institutions. This research uses descriptive qualitative method with a case study approach.